STUDI KEKUATAN HASIL LAS OXY-ACETYLENE PADA VARIASI KAMPUH - Nofriady Handra; Peri Indra Yudi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2011)
The welding use gas of Oxy-Acetylene as source of heat represent one of the way of weld which quite a lot used at field. The test at the result of oxy-acetylene conducted with a few form different of groove, to know strength of weld form groove of test. Objective of the research is to knowing strength of result weld Oxy-Acetylene at steel of ST 37 which is joint on form groove of U,V and X. The result test of strength steel ST 37 with thick the sample is 5 mm which is with Oxy-Acetylene form of groove U,V and X this can be concluded, the tensile strength of weld steel which is smaller than tensile strength of the steel without weld, and weld steel result have the character of brittle and coarse grain. Tensile strength result of biggest welding happened at test of weld with form groove V that is equal to 317.7 N / mm2 . Joint of weld with form groove U have : Fmaks = 16768.8 N, groove V : Maks F = 19856.3 N and groove X : Maks F = 17381.2 N.